Cameron and the Conservatives
XVI, 268 p.
Keywords: Specialists in Conservative Party politics examine the effectiveness of the Cameron led coalition. The contributors examine Cameron as leader and Prime Minister; the Conservatives' modernisation strategy; the level of ideological coherence in 'liberal conservatism'; and the impact of the coalition on a range of policy areas and on 'New' Labour.